A Study of Christian Witness in the Field of International Development - Reader, Gregory J. (My University, 2021)
International development organizations do more than effect changes in people’s social, political, economic, environmental, educational, and health conditions. By their actions, they also convey values and sets of beliefs about the nature of human wellbeing and how it can be realized. While there may be considerable similarities in beliefs, values, and activities across the spectrum of development agencies, there are also differences between secular, Christian, Muslim, Buddhist, and other faith-based organizations. Especially as postcolonial criticism exposes the negative consequences of categorizing others as less developed, and setting agendas of change for them, it is important for organizations to understand what meaning is conveyed through their actions and their consequences. Some Christian organizations understand their faith as a motivating factor or an identity marker, but do not intend to communicate distinctively Christian beliefs and values through their work in international development. Others believe their work is an engagement in Christian mission, and do intend to convey distinctively Christian meaning through it. This study suggests and tests a process for assessing whether the intended meaning is being understood by people the organization is active among. Two organizations participated in this study: International Teams Canada and World Renew Canada. Employing an adapted phenomenological methodology, an inquiry was designed to learn what people perceive to be the organizations’ beliefs, values, and aims, based on their experience of the organization’s activities in their community. The inquiry was conducted in two communities in Guatemala in which the organizations are engaged. The participants’ experiences and perceptions are significant for the field of international development because they provide insight into what people living in conditions of poverty consider to be important qualities of improved standards of living. The findings are significant to the field of practical theology because they provide further insight into how meaning is conveyed in and through practice. Lastly, the study contributes to the understanding of Christian witness in international development in two ways. First, it tests a framework for evaluating the effectiveness of an organization’s activities as Christian witness, and offers an adapted research guide as an appendix. Second, it brings more marginalized voices into the missiological discourse and thereby provides a rich opportunity for theological reflection on how community voices influence organizations’ perspectives on the significance of Jesus in efforts to overcome poverty.